Pengembangan Sistem Informasi Pemantauan Alat Kesehatan Untuk Mendukung Penjaminan Mutu Pelayanan Kesehatan Di Balai Kesehatan Indera Masyarakat (BKIM) Provinsi Jawa Tengah - Hamdan Syah Alam; Sudiro Sudiro; Cahya Tri Purnami (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
An information system of monitoring health equipment at Balai Kesehatan Indera Masyarakat (BKIM) in Province of Central Java was very simple. The available system had not resulted complete, accurate, and well-timed information in accordance with the needs of management to monitor health equipment in all health service rooms. The aim of this study was to develop an information system of monitoring health equipment to support quality assurance of health services at BKIM in the Province of Central Java. This was a qualitative-quantitative study using Pre-Experimental design with one group pretest-posttest approach. Data were collected using methods of observation and interview. Furthermore, qualitative data were analysed using content analysis whereas quantitative data were presented descriptively using a balanced average value. The result of this study showed that a balanced average value before developing the system was 37.73 and after developing the system was 78.90 with the difference equal to 41.17. There needs commitment and support from the head of BKIM in Central Java Province. Implementation of the developed system needs to be continually monitored. Socialisation and training needs to be conducted for all employees who have main tasks and functions relating to health equipment. In addition, budget for operational costs and system maintenance needs to be allocated.